Osmotic gradients induce bio-reminiscent morphological transformations in giant unilamellar vesicles - Oglęcka, Kamila (2013)
We report observations of large-scale, in-plane and out-of-plane membrane deformations in giant uni- and multilamellar vesicles composed of binary and ternary lipid mixtures in the presence of net transvesicular osmotic gradients. The lipid mixtures we examined consisted of binary mixtures of DOPC and DPPC lipids and ternary mixtures comprising POPC, sphingomyelin and cholesterol over a range of compositions – both of which produce co-existing phases for selected ranges of compositions at room temperature under thermodynamic equilibrium. In the presence of net osmotic gradients, we find that the in-plane phase separation potential of these mixtures is non-trivially altered and a variety of out-of-plane morphological remodeling events occur. The repertoire of membrane deformations we observe display striking resemblance to their biological counterparts in live cells encompassing vesiculation, membrane fission and fusion, tubulation and pearling, as well as expulsion of entrapped vesicles from multicompartmental giant unilamellar vesicles through large, self-healing transient pores. These observations suggest that the forces introduced by simple osmotic gradients across membrane boundaries could act as a trigger for shape-dependent membrane and vesicle trafficking activities. We speculate that such coupling of osmotic gradients with membrane properties might have provided lipid-mediated mechanisms to compensate for osmotic stress during the early evolution of membrane compartmentalization in the absence of osmoregulatory protein machinery.